Pengalaman Mahasiswa dalam Kelas Inklusif: Studi Fenomenologi tentang Rasa Aman, Akses Belajar, dan Keadilan - Azazi, Abdul Kohar; Nugraha, Mulyawan Safwandy; Anwarudin, UK (JIPENDIKA : Jurnal Inovasi Pembelajaran dan Pendidikan, 2025)
This phenomenological study examines how university students from diverse social, cultural, and academic backgrounds experience an inclusive classroom in the course “Pengembangan Keberagaman Peserta Didik” at Institut KH Ahmad Sanusi Sukabumi. Data were collected through in-depth interviews with three students with contrasting socio-economic conditions and communication norms, interviews with two lecturers, and one cycle of classroom observation. We conducted thematic analysis through repeated reading, open coding, clustering, and triangulation across sources. The findings show that psychological safety grows when lecturers respond to mistakes without judgment, yet it becomes fragile when discussions are dominated by a few students and when identity-related jokes target accent or social class. Learning access is constrained by fast pacing, dense academic language, and unequal access to devices, which pushes some students to rely on phones, peers, and self-study to keep up. Perceived fairness strengthens when lecturers provide transparent rubrics, written feedback, opportunities for revision or remedial work, and reasonable accommodations such as flexible deadlines. Cultural norms of politeness and respect for hierarchy also shape participation, often leading students to disagree indirectly. These results support more structured discussion protocols, anti-mockery norms, low-tech alternatives, and explicit assessment guidance.